Pengaruh Metode Experiential Learning dalam Pembelajaran Hadits di Pondok Pesantren Modern Al-Amanah Terhadap Aspek Kognitif Santri - Fatichatus Sa’diyah (INTEGRATIA: Journal of Education, Human Development, and Community Engagement, 2023)
Islamic boarding schools are the oldest educational institutions that preserve classical learning methods in their application. In its application, the use of classical methods results in several problems. Among them are students feeling bored, lack of learning innovation, and so on. At the al-Amanah Sidoarjo Modern Islamic Boarding School, the ustaz teaches the material to children using a relatively new method. In this research, the author will discuss the impact of the experiential learning method in teaching Hadith at the al-Amanah Modern Islamic Boarding School on the cognitive aspects of students. The study of hadith was chosen not without reason, firstly, hadith is the main study in the sources of Islamic teachings. Second, there is almost no Islamic boarding school that does not teach hadith as its own subject. This research will answer one big question related to the impact of the experiential learning method in teaching hadith at the al-Amanah Islamic Boarding School on the cognitive aspects of students. This type of research is qualitative, while the approach in this research is empirical. The data collection methods are direct observation, interviews, and documentation. The data analysis is qualitative data analysis which is descriptive-qualitative in nature. In this research, the author uses the experiential learning method, namely a learning process model that emphasizes the central role of experience in the learning process. The results of this research are that there are three methods used by hadith teachers in this Islamic boarding school which are closely related to the experiential learning method. These include stories, drills and presentations. By using these three methods, students' cognitive aspects continue to improve, namely at the level of memory, understanding, application, analysis, evaluation and creation.